2021
DOI: 10.1016/j.still.2020.104841
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tillage based crop establishment and residue management practices on soil quality indices and yield sustainability in rice-wheat cropping system of Eastern Indo-Gangetic Plains

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 64 publications
(64 reference statements)
2
12
0
Order By: Relevance
“…In the relatively short time of 2.5 years (after Crop 7), the SP and HR practice resulted in increased SOC concentrations at 0-0.15 m soil depth when compared to current practice involving intensive tillage along with 2021) reported significant increases in SOC after three years under SP (24%) and zero tillage (23%) as compared to CT at 0-0.05 m soil depth in the rice-lentil/wheat-jute systems of Bangladesh. Likewise, Saurabh et al (2021) reported a 18% increase in SOC at 0-0.1 m soil depth under zerotill direct seeded rice followed by zero-till wheat as compared to puddled transplanted rice followed by conventional wheat after four years in a rice-wheat system of Eastern Indo-Gangetic Plain. Increases in SOC pools with CA after four years in a rice-wheat cropping system of Northwest India were also reported by Jat et al (2019).…”
Section: Temporal Changes Of Socmentioning
confidence: 93%
“…In the relatively short time of 2.5 years (after Crop 7), the SP and HR practice resulted in increased SOC concentrations at 0-0.15 m soil depth when compared to current practice involving intensive tillage along with 2021) reported significant increases in SOC after three years under SP (24%) and zero tillage (23%) as compared to CT at 0-0.05 m soil depth in the rice-lentil/wheat-jute systems of Bangladesh. Likewise, Saurabh et al (2021) reported a 18% increase in SOC at 0-0.1 m soil depth under zerotill direct seeded rice followed by zero-till wheat as compared to puddled transplanted rice followed by conventional wheat after four years in a rice-wheat system of Eastern Indo-Gangetic Plain. Increases in SOC pools with CA after four years in a rice-wheat cropping system of Northwest India were also reported by Jat et al (2019).…”
Section: Temporal Changes Of Socmentioning
confidence: 93%
“…The second set of experiments based on diversified CA cropping systems was established in 2015, where an experiment comprising seven tillage and crop establishment (TCE) methods for a rice–wheat-mungbean system was established in a randomized complete block design (RCBD) with three replications. Briefly, seven treatments in different management practices were divided as follows: Sc1) random puddled transplanted rice (RPTR)-conventional tilled (CT) broadcast wheat (BCW)-zero-till mungbean (ZTM); Sc2) line puddled transplanted rice (LPTR)-CT drilled wheat (CTW)-ZTM; Sc3) conventional tilled machine transplanted rice (CTMTR)-zero-till wheat (ZTW)-ZTM; Sc4) zero-till machine transplanted rice (ZTMTR)-ZTW-ZTM; Sc5) system of rice intensification (SRI)-system of wheat intensification (SWI)-ZTM; Sc6) CT direct-seeded rice (CTDSR)-ZTW-ZTM; Sc7) zero-till DSR (ZTDSR)-ZTW-ZTM 15 , 20 (Supplementary Table 2 ). The third set of CA experiments was established in the rainy season of 2016 to address the rice-fallow production system, where rice-chickpea, rice-lentil, rice-safflower, rice-linseed, and rice-mustard sequences were followed under diverse tillage production systems (ZTDSR, CTDSR and TPR with and without residue management practice 27 (Supplementary Table 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…As a technological innovation, CA-based production systems, which retains residue of previous crops, minimum mechanical disturbance of the soil, and crop diversification, are being promoted in the MIGP 14 , 15 . CA practices not only enhance the soil quality but also favour the habitats for soil-dwelling organisms 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%
“…But the continuous adoption of this system has resulted in several negative effects on soil health (Nandan et al, 2021). Repeated puddling in coarse and medium-textured soils has resulted in subsurface compaction, which affects the cultivation of successive upland crops, such as wheat, by restricting the root growth and causing aeration problems (Hossain et al, 2021;Saurabh et al, 2021). Puddled transplanted rice, when following a wheat crop, exposes the hidden organic matter to air and results in its oxidation, thus leading to structural degradation of the soil.…”
Section: Soil Healthmentioning
confidence: 99%